Pengaruh Strategi Reciprocal Teaching terhadap Hasil Belajar Tematik Terpadu Kelas V SDN Gugus 6 Pesisir Selatan - Kristiando, Wahyu; Fitria, Yanti (Lembaga Yasin AlSys, 2024)
Research in the background by student learning outcomes that are not optimal. The purpose of the study was to determine the effect of the use of the Recipcoal Teaching Strategy on the learning outcomes of grade V students of SDN cluster 6 Pesisir Selatan. The type of research is quantitative research in the form of quasi-experimental design research using the non-equivalent control group design. The research was conducted at SDN 04 Pasar Taluk and SDN 22 Pasar Taluk. Sample data collection was carried out using the cluster random sampling technique. The instrument used is in the form of an objective test in the form of multiple choice. The data analysis technique used is t-test. Based on the results of the pretest obtained, the experimental class that applied the Reciprocal Teaching Strategy was 54.37 and the average posttest was 78.22 while the learning in the Control class using the conventional approach had an average pretest learning outcome of 53.89 and an average posttest of 68.41 Based on the hypothesis test carried out with the t-test obtained by calculating the ttable > which was 3.43 > 2,000 real level 0.05 It can be concluded that the Reciprocal Teaching Strategy has an effect on the results Students learn in integrated thematic learning in elementary school.